Cecal Metabolomic Fingerprint of Unscathed Rats: Does It Reflect the Good Response to a Provocative Decompression? - Desruelle, Anne-Virginie; Maistre, Sébastien de; Gaillard, Sandrine; Richard, Simone; Tardivel, Catherine; Martin, Jean-Charles; Blatteau, Jean-Eric; Boussuges, Alain; Rives, Sarah; Risso, Jean-Jacques; Vallee, Nicolas (Frontiers in Physiology, 2022)
On one side, decompression sickness (DCS) with neurological disorders lead to a reshuffle of the cecal metabolome of rats. On the other side, there is also a specific and different metabolomic signature in the cecum of a strain of DCS-resistant rats, that have not been exposed to hyperbaric protocol. We decided to study a conventional strain of rats that resist to an accident-provoking hyperbaric exposure, and we hypothesize that the metabolomic signature put forward may correspond to a physiological response adapted to the stress induced by diving. The aim is to verify and characterize whether the cecal compounds of rats resistant to the provocative dive have a cecal metabolomic signature different from those who have not dived. 35 asymptomatic diver rats were selected to be compared to 21 rats non-exposed to the hyperbaric protocol. Because our aim was essentially to study the differences in the cecal metabolome associated with the hyperbaric exposure, about half of the rats were fed soy and the other half of maize in order to better rule out the effect of the diet itself. Lower levels of IL-1β and glutathione peroxidase (GPX) activity were registered in blood of diving rats. No blood cell mobilization was noted. Conventional and ChemRICH approaches helped the metabolomic interpretation of the 185 chemical compounds analyzed in the cecal content. Statistical analysis showed a panel of 102 compounds diet related. 19 are in common with the hyperbaric protocol effect. Expression of 25 compounds had changed in the cecal metabolome of rats resistant to the provocative dive suggesting an alteration of biliary acids metabolism, most likely through actions on gut microbiota. There seemed to be also weak changes in allocations dedicated to various energy pathways, including hormonal reshuffle. Some of the metabolites may also have a role in regulating inflammation, while some could be consumed for the benefit of oxidative stress management.